2021
DOI: 10.3390/medicina57060529
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation and Complementary Physical Training in Elderly Patients after Acute Coronary Syndrome: A Pilot Study

Abstract: Background and Objectives: Nearly 23% of elderly patients hospitalized due to acute coronary syndrome have reduced muscle strength. It is assumed that these patients would better benefit from a complex training—a combination of endurance, strength, balance, coordination, and flexibility—in order to reduce the loss of muscle strength and mass and improve functional capacity. The aim of this study was to assess the effectiveness and safety of two different complementary resistance and balance training programs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A mean 18-d rehabilitation program in various patients with HF (angina pectoris, myocardial infarction, and cardiac surgery) led to a 31% increase in the 6-min walk test. 16,17 Similarly, a multicenter study confirmed a more modest, but very significant, +16% improvement in a large and varied cohort of patients with HF following completion of a 3-to 4-wk CR program. 18 These data are in accordance with our observations, although the CR duration of our protocol was shorter.…”
Section: Application To Clinical Practicementioning
confidence: 86%
“…A mean 18-d rehabilitation program in various patients with HF (angina pectoris, myocardial infarction, and cardiac surgery) led to a 31% increase in the 6-min walk test. 16,17 Similarly, a multicenter study confirmed a more modest, but very significant, +16% improvement in a large and varied cohort of patients with HF following completion of a 3-to 4-wk CR program. 18 These data are in accordance with our observations, although the CR duration of our protocol was shorter.…”
Section: Application To Clinical Practicementioning
confidence: 86%
“…The present study was carried out from January 2020 to September 2021 and is continuation of a larger clinical, randomized controlled trial conducted in a single rehabilitation center (Kulautuva Rehabilitation Hospital, Lithuanian University of Health Sciences, Kaunas, Lithuania) [15]. The study was approved by Kaunas Regional Biomedical Research Ethics Committee (permission No.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Every item on the scale is rated by a score of 0 to 2; the maximal score achievable is 17, and this indicates severe frailty. During this study, the patients were classified based on their EFS score into the following categories as suggested on the official EFS website (Edmontonfrailscale.org): fit (score of 0 to 3), vulnerable (score of 4 to 5), and frail (score of 6 to 17) [15]. In addition, all of the participants passed a clinical evaluation of gait speed, using the 5 m walk test (5MWT).…”
Section: Study Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis of 10 randomized controlled trials, patients with CAD who exercised following PCI resulted in improved left ventricular ejection fraction, decreased incidence of cardiac death, myocardial infarction (MI), coronary angioplasty, angina pectoris and restenosis compared to controls [17]. Likewise, cardiac rehabilitation in elderly patients after ACS has resulted in significant improvements in functional capacity and physical performance [18]; however, the longitudinal patterns of physical activity, sedentary behaviours and sleep in older patients (≥75 years) following PCI are scarce. The purpose of the present study was to evaluate the physical activity levels, inactivity and sleep patterns of older patients with CAD following PCI, longitudinally over 12 months.…”
Section: Introductionmentioning
confidence: 99%